2021
DOI: 10.4103/ijo.ijo_885_20
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric evaluation in patients with central serous chorioretinopathy in Asian Indians

Abstract: Purpose: This study aimed at psychiatric evaluation of patients with central serous chorioretinopathy (CSCR) and its association. Material: Consecutive patients diagnosed to have CSCR were included in the study. The participants underwent a routine eye examination. After informed consent, participants were subjected to psychiatric evaluation by a qualified psychiatrist. Details of evaluation and psychiatric disorders were documented and if treatment required were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…In contrast to previous publications, we did not find evidence for higher levels of depression [ 14 , 15 ] and anxiety [ 14 , 15 , 17 , 18 ] in CSC patients compared to our control groups (Fig. 1 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous publications, we did not find evidence for higher levels of depression [ 14 , 15 ] and anxiety [ 14 , 15 , 17 , 18 ] in CSC patients compared to our control groups (Fig. 1 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Most studies of individual psychological traits (rather than just personality types) compared CSC patients with healthy age- and sex-matched controls [ 14 , 17 ], if they had control groups at all [ 15 , 16 , 18 ]. Consistent with these reports [ 14 16 ], we also found higher stress level in CSC patients compared to a control group without retinal disease (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuation of our paper in this journal on psychiatric evaluation of central serous chorioretinopathy (CSCR) patients in Asian Indians,[ 1 ] the results show a higher incidence of anxiety and depressive disorders in CSCR individuals. As a corollary to that, we are suggesting treating the subset of patients with Type A personality[ 2 ] with anxiolytic (acting on GABA pathway) and anti-depressant (serotonin pathway action) drugs.…”
mentioning
confidence: 81%
“…Chronic patients experienced more stressful events and lesion size was linked with anxiety scores [ 42 ]. Studies conducted among the Asian population revealed that patients with CSCR have a high tendency to develop mixed anxiety disorders, depression, schizophrenia, and hysteria [ 43 – 45 ].…”
Section: Psychiatric Disordersmentioning
confidence: 99%